Disaster Resilience in Vulnerable cities through Neighbourhood Development: A case of Chennai. (2016) - Greeshma, P.; Kumar, K. Manoj
Abstract: This paper follows the discipline of Urban Design to elaborate the concepts of disaster resilience at the neighbourhood level for the collective development of Chennai city. The increased inflow and use of resources attributed to the growing urban population creates a pressure on the various natural systems, increasing their vulnerability to multiple attacks from natural and man-made forces. Hence the future adaptability of cities is important for its growth in the aftermath of a disaster strike. The intent of this research is thus to develop a framework of strategies for an emergency response programme and to develop a design scheme to make cities resilient, through neighbourhood development. A sample precinct of Chepauk was taken up for the design demonstration after a detailed analysis of the same, addressing various physical factors such as land use, open spaces, connectivity networks, physical and social infrastructure, built density, ecology and emergency response mechanism.